Auctions in an outcome-based payment scheme to reward ecological services in agriculture – Conception, implementation and results - Markus Groth (European Regional Science Association (ERSA), 2005)
This paper presents an outcome-based payment scheme to reward ecological services in agriculture. It was designed by a research group from the Georg-August-University of Goettingen. Starting in January 2004 the payment scheme is tested upon it's implementation as an agri-environmental program in a model-region (administrative district Northeim in the south of Lower Saxony – Germany). The intention of the program is to overcome the disadvantages of existing and mostly action-orientated agri-environmental programs, especially those in the European Union. The design of the payment scheme is based on fundamental criteria of market economy such as supply and demand and it integrates auctions as an award procedure. Furthermore it is outcome-based and considers the interests of the local people and the relevant stakeholders and their demand for botanical diversity. The main research topic is to explore the use of auction in agri-environmental programs seen from an transaction cost economics point of view. Therefor the relevant farmers transaction costs will be measured. In the course of this research it is essential to analyse the practical relevance of transaction costs and to draw conclusions to their theoretical foundation. Results as well as of the first auction and two surveys of local farmers already show, that this payment scheme is not just an theoretical construct but that it is already practicable in the model-region. However further research is needed to make sure that at the end of the current case study this payment scheme is authorised from an ecological economics point of view and has a high potential to be a part of a sustainable future agri-environmental policy in Germany and the European Union.
Keywords: 330